Changes in hemocoagulation in acute stroke patients after one-hour sono-thrombolysis using a diagnostic probe - Skoloudík, David; Fadrná, Tána; Roubec, Martin; Bar, Michal; Zapletal, Ondrej; Blatný, Jirí; Langová, Katerina; Bardon, Petr; Sanák, Daniel; Kanovský, Petr; Herzig, Roman (Ultrasound in medicine & biology.., 2010)
The aim was to monitor the changes in hemocoagulation parameters in acute ischemic stroke (AIS) patients after sono-thrombolysis of the occluded middle cerebral artery using a duplex transcranial probe with 2.0-MHz frequency in Doppler mode. Sixteen AIS patients indicated for intravenous thrombolysis (IVT) (8 males; mean age 68.3 +/- 7.1 y) and 16 AIS patients contraindicated for IVT (11 males; mean age 67.9 +/- 7.9 y) were randomized for sono-thrombolysis (8 + 8 patients) or standard treatment (control group) (8 + 8 patients). The significant decrease of plasminogen activator inhibitor-1, plasminogen and alpha-2-antiplasmin activity by a mean of 60, 32 and 24%, respectively, and the increase of tissue plasminogen activator by a mean of 56% was found after sono-thrombolysis when compared with control group (p < 0.0125); these changes were more evident in patients treated with a combination of sono-thrombolysis and IVT (79, 38, 50 and 82%, respectively) than in patients treated by sono-thrombolysis alone (34, 13, 17 and 30%, respectively).
Keywords: Equipment Design; dospělí; Acute Disease; Female; Thrombolytic Therapy; analýza selhání vybavení; Ultrasonic Therapy; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; vibrace ultrazvukové; cévní mozková příhoda; Adolescent; Blood Coagulation; trombolytická terapie; lidé; Stroke; ultrazvuková terapie; Treatment Outcome; Equipment Failure Analysis; Sonication; Male; Aged; Young Adult; akutní nemoc; lidé středního věku; echoencefalografie; senioři; mužské pohlaví; Echoencephalography; design vybavení; hemokoagulace; Middle Aged; mladiství; Humans